The Effect of Pacotera Gymnastics on The Psychology of Home-Schooling Students - Wahjuni, Endang Sri; Febriyanti, Irma; Yuhantini, Eva Ferdita; Rosyida, Elfia (Journal of Sport Science and Education, 2022)
The Covid-19 pandemic causes students to experience online learning from home. This causes a decrease in physical activity and psychological impact. Necessary as to provide a stimulus by an exciting exercise, especially for children at the elementary school level a rhythmic gymnastics called Pandemic Corona tetap Gembira (Pacotera), modified rhythmic gymnastics for children aged 6-12 years, on children's psychology. The research method was a quasi-experimental design with one group pretest-posttest design and the sampling technique was purposive sampling with a sample of 30 students of SDN Wiyung I Surabaya. Data collection using a questionnaire Pediatric Symptoms Checklist 17. Based on the results of the T test that used to determine the differences in pre and post treatment of Pacotera gymnastics, showed that there were significant differences in the attention aspect (Sig. 0.01 <0.05) and the externalization aspect (Sig. 0.03 <0.05), but there is no significant difference in the internalization aspect (Sig. 0.601> 0.05). The conclusion is Pacotera gymnastics can improve Children’s psychological condition while learning from home.This study contributes to elementary school teachers encourage their students to do Pacotera gymnastics before learning.